Application of Manganese-Based Materials in Aqueous Rechargeable Zinc-Ion Batteries - Zhang, Wanhong; Zhai, Xiaoliang; Zhang, Yansong; Wei, Huijie; Ma, Junqing; Wang, Jing; Liang, Longlong; Liu, Yong; Wang, Guangxin; Ren, Fengzhang; Wei, Shizhong (Frontiers in Energy Research, 2020)
In recent years, aqueous rechargeable zinc-ion batteries (AZIBs) have attracted more and more attention not only because they use earth-abundant metals but also due to their improved safety and high volumetric energy density. As one type of promising electrode material for AZIBs, manganese-based materials are receiving considerable attention owing to their high theoretical specific capacity, non-toxicity, and low cost. This mini review summarizes the recent advances on the application of manganese-based materials (manganese oxide, manganate, and their composites) in AZIBs. In addition, the methods to enhance their zinc-ion storage properties are summarized and discussed, such as morphology engineering, doping, as well as compositing with other materials. Ultimately, some personal prospects for future research of the manganese-based materials for AZIBs are also proposed.